An improved viscous boundary for dynamic soil-struct ure interaction 1 - Dieterman, Harry A.; Gajewski, R. Robert (Computer Assisted Methods in Engineering and Science, 2023)
In many engineering problems modelling of wave propagation in infinite or semi-infinite domains is of great importance. One of the main limitations of the usage of the finite element method in dynamic soil-structure interaction arises when it is used for the modelling of an infinite domain. If nothing is done to take care of artificial reflections at the mesh boundaries, errors are introduced into the results. To handle the reflections different artificial boundaries have been proposed in the literature and used. This paper deals with an improvement of one of the most widely used local absorbing boundary condition -the standard viscous boundary. Both analytical investigations of the efficiency of the boundary as well as numerical results are presented.